2014
DOI: 10.1007/978-1-4939-0897-4_10
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Neuroactive Compounds Produced by Psychobiotics

Abstract: We recently coined the phrase 'psychobiotics' to describe an emerging class of probiotics of relevance to psychiatry [Dinan et al., Biol Psychiatry 2013;74(10):720-726]. Such "mind-altering" probiotics may act via their ability to produce various biologically active compounds, such as peptides and mediators normally associated with mammalian neurotransmission. Several molecules with neuroactive functions such as gamma-aminobutyric acid (GABA), serotonin, catecholamines and acetylcholine have been reported to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
156
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 268 publications
(171 citation statements)
references
References 126 publications
0
156
1
6
Order By: Relevance
“…One obvious limitation of our current study is that we did not examine these isolates for their ability to secrete catecholamines and serotonin, which are important neurotransmitters. However, recent studies by others have clearly shown the presence and importance of these metabolites from gut-associated microbes, including the bidirectional character of microbiota–host interactivity via neuromediators including BAs [37,38]. …”
Section: Discussionmentioning
confidence: 99%
“…One obvious limitation of our current study is that we did not examine these isolates for their ability to secrete catecholamines and serotonin, which are important neurotransmitters. However, recent studies by others have clearly shown the presence and importance of these metabolites from gut-associated microbes, including the bidirectional character of microbiota–host interactivity via neuromediators including BAs [37,38]. …”
Section: Discussionmentioning
confidence: 99%
“…are known to produce dopamine and gut microbiota accounts for almost half of the dopamine production in the body. 69,70 Cyanobacteria, present in minute quantities in the GI tract, is believed to produce β-N-methyl amino-L-alanine (BMAA) which has been found to be increased in the brain of PD, Alzheimer's disease, and amyotrophic lateral sclerosis patients. BMAA is an excitotoxin which activates metabotropic glutamate receptor 5 that causes reduction in the levels of glutathione, a major antioxidant.…”
Section: Gut Microbiome Dysbiosismentioning
confidence: 99%
“…77,96 Dopamine is also produced in large quantities by a variety of bacteria including E coli, Bacillus cereus, Bacillus subtilis, and Staphylococcus aureus. 97 However, the host produces enzymes that degrade these bacterial neurochemicals. For example, dopamine is silenced by the host-produced enzyme monoamine oxidase.…”
mentioning
confidence: 99%